2019
DOI: 10.3390/insects10090258
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Identification of MicroRNAs in Apis cerana cerana Workers’ Midguts in Response to Nosema ceranae Invasion

Abstract: Here, the expression profiles and differentially expressed miRNAs (DEmiRNAs) in the midguts of Apis cerana cerana workers at 7 d and 10 d post-inoculation (dpi) with N. ceranae were investigated via small RNA sequencing and bioinformatics. Five hundred and twenty nine (529) known miRNAs and 25 novel miRNAs were identified in this study, and the expression of 16 predicted miRNAs was confirmed by Stem-loop RT-PCR. A total of 14 DEmiRNAs were detected in the midgut at 7 dpi, including eight up-regulated and six d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 103 publications
0
30
0
Order By: Relevance
“…The prepared spores of N. ceranae were subjected to microscopic observation using an optical microscope (SIOM, Shanghai, China). Furthermore, the total RNA of spores were isolated and used as templates for reverse transcription; the resulting cDNA was then used as templates for PCR amplification with previously described specific primers for N. ceranae and N. apis [ 22 , 23 ] and the amplified products were detected by 1.5% agarose gel electrophoresis (AGE). Sterile water was set as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The prepared spores of N. ceranae were subjected to microscopic observation using an optical microscope (SIOM, Shanghai, China). Furthermore, the total RNA of spores were isolated and used as templates for reverse transcription; the resulting cDNA was then used as templates for PCR amplification with previously described specific primers for N. ceranae and N. apis [ 22 , 23 ] and the amplified products were detected by 1.5% agarose gel electrophoresis (AGE). Sterile water was set as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The prepared spores of N. ceranae was subjected to microscopic observation using an optical microscope (SIOM, Shanghai, China). Further, total DNA of spores were isolated and used as templates for reverse transcription; the resulting cDNA was then used as templates for PCR amplification with previously described specific primers for N. ceranae and N. apis [22][23]; the amplified products were detected by 1.5% agarose gel electrophoresis (AGE). Sterile water was set as a negative control.…”
Section: Microscopic Observation and Pcr Validation Of N Ceranae Sporesmentioning
confidence: 99%
“…Before and during the whole experiment, no Varroa was detected. RT-PCR was performed to examine the prevalence of two bee microsporidia (N. ceranae and Nosema apis) and seven common bee viruses (ABPV, BQCV, CBPV, DWV, KBV, IAPV, and SBV) in the newly emergent A. c. cerana workers using previously developed specific primers (Table S1) [38][39][40][41][42][43][44]. Agarose gel electrophoresis (AGE) showed that no signal bands were amplified from the above-mentioned two microsporidia and seven viruses (Figure S1).…”
Section: Transcriptome Data Sourcementioning
confidence: 99%
“…Workers' midgut at 12 dpi without N. ceranae was set as a negative control, and sterile water as another negative control. PCR amplification was conducted on a T100 thermo cycler (BIO-RAD) with previously described primers for N. ceranae (F: CGAGCGGTTTCCCATCTCAGTA; R: AAAACACCG-GAACTCGTCAGCT) [38] and the following conditions: pre-denaturation step at 94 • C for 5 min; 37 amplification cycles of denaturation at 94 • C for 50 s, annealing at 59 • C for 30 s, and elongation at 72 • C for 1 min; followed by a final elongation step at 72 • C for 10 min. The PCR products were examined on 1.5% AGE with Genecolor (Gene-Bio) staining.…”
Section: Confirmation Of Effective Infection Of Eastern Honeybee Workers By N Ceranaementioning
confidence: 99%